Synthesis and anticancer activity of lavendustin A derivatives containing arylethenylchromone substituents - Lee, Ki Yong; Nam, Dong Hyuk; Moon, Chang Sang; Seo, Seon Hee; Lee, Jae Yeol; Lee, Yon Sun (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2006)
2-Styrylchromones, which are relatively scarce in nature, have been reported to possess potent cytotoxicities on KB cell line. Lavendustin A, a metabolite of Streptomyces griseolavendus, has been shown to inhibit a growth of A431 cell line. Accordingly, a series of compounds 3a-g having structural features of styrylehromones and lavendustin A were synthesized and evaluated for cytotoxicity using SRB assay on four tumor cell lines. Compounds 3a-g were synthesized by the condensation of 2-methylchromone derivative 7 with several aromatic aldehydes. Among synthesized, compound 3e showed the significant cytotoxic activity on HCT-15 cell line with IC50 values of 7.17 mu g/ml indicating that lavendustin A derivatives containing 2-arylethenylchromone ring have a potential in anti-tumor application. (c) 2006 Elsevier SAS. All rights reserved.
Keywords: HORMOTHAMNIONE